Self assessment & review medicine - Khanna, Mudit (Jaypee, 2016)
The structure of Postgraduate Medical Entrance Examinations has undergone a dramatic change over the past few years with the pattern of examination moving from a 'Paper Based' All India Postgraduate Medical Entrance Examination (AIPGMEE) conducted by All India Institute of Medical Sciences (AIIMS), to a 'Computer based' AIPGMEE conducted by National Board of Examinations (NBE). To help you prepare for the test in a more efficient manner we have made certain key changes in the format of the book.